PEMBELAJARAN MITIGASI BENCANA BANJIR TERHADAP SISWA SEKOLAH DASAR - Nadia Try; Fitria; Feronika Manalu; Tin Rustini; Yona Wahyuningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This research aims to describe flood disaster mitigation to improve students' understanding of flood disaster preparedness. This research uses literature study methods. Data collection and information is carried out by reading, recording, and processing research materials based on written work from research results both that have been and have not been published. The results show that. Flood mitigation learning in schools can be done through learning in schools such as thematic learning, the use of comic media, extracurricular scouts, and seminars. Children with Special Needs also needs to be taught about disaster mitigation. Children with Special Needs also has the same right as other children to be able to learn about how to protect themselves and save themselves when disasters occur. Basic education also needs to teach about the formation of self-concept